2022
DOI: 10.3390/resources11100091
|View full text |Cite
|
Sign up to set email alerts
|

Valorizations of Marigold Waste for High-Value Products and Their Industrial Importance: A Comprehensive Review

Abstract: The municipal authorities in developing nations face serious challenges in marigold flower garbage management. The primary issue is that they never are reused after prayers. Flower waste of Tagetes erecta, T. patula, and Calendula officinalis L. are commonly used for carotenoid and flavonoid extractions and, subsequently, used for incense stick and biogas production. Marigold plants are also used for phytoremediation during their growth stage. The lutein industry is booming due to its increasing market demand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 104 publications
0
0
0
Order By: Relevance
“…These plants are a rich source of lutein which is very important for the human eyes and immunity, thus its already commercially used and produced as a nutritional supplement in capsule or tablet form (Cannavale et al 2019;Wu et al 2023). Since the human body cannot synthesize those chemicals, it must be obtained from the diet, however, it is known lutein is also contained naturally in fruits, cereals and some vegetables (Gupta et al 2022;Chauhan et al 2022). High levels of lutein (oxygenated carotenoid xanthophyll) are contained in the petals of marigold and can be used for food coloring agents as well as for antioxidants (Ingkasupart et al 2015;Cezare-Gomes et al 2019;Casella et al 2021;Gupta et al 2022).…”
Section: Food and Beveragementioning
confidence: 99%
“…These plants are a rich source of lutein which is very important for the human eyes and immunity, thus its already commercially used and produced as a nutritional supplement in capsule or tablet form (Cannavale et al 2019;Wu et al 2023). Since the human body cannot synthesize those chemicals, it must be obtained from the diet, however, it is known lutein is also contained naturally in fruits, cereals and some vegetables (Gupta et al 2022;Chauhan et al 2022). High levels of lutein (oxygenated carotenoid xanthophyll) are contained in the petals of marigold and can be used for food coloring agents as well as for antioxidants (Ingkasupart et al 2015;Cezare-Gomes et al 2019;Casella et al 2021;Gupta et al 2022).…”
Section: Food and Beveragementioning
confidence: 99%
“…At P3 (dose 1.0 g/Kg-BW), an average of 0.55 was found. At P3, there was a decrease again; this needs to be suspected of the presence of other ingredients besides flavonoids in the ethanol extract of marigold leaves [16]. Explained that there are several country markets that sell flowers from the marigold plant to be used as mosquito repellent and vegetable insecticides [28].…”
Section: Effect Of Administration Of Ethanol Extract Of Marigold Leav...mentioning
confidence: 99%
“…Spermatogenesis is strongly influenced by the role of FSH, namely by stimulating Sertoli cells to produce ABP, inhibin synthesis, glycoprotein synthesis, and energy metabolism, and then produces lactic acid which is a source of energy for spermatogenic cells reported that the laboratory reference for normal adult men is (FSH 1.38-9.58 mIU/ml) [11][12][13]. Marigold (Tagetes erecta) or often called the kotok flower as shown in Figure 1 is a plant that grows wild on plantations or around the house [14] indicated that marigold is a type of medicinal plant that contains flavonoids, polyphenols, and two types of carotenoids, namely carotenes, and xanthophylls [15,16]. Flavonoids present in marigold leaves have been shown to be free radical scanning caused by several factors, one of which is exposure to cigarette smoke [17,18] showed that flavonoids are antioxidants that can reduce lipid oxidation and suppress the formation of free radicals [17] reported that total polyphenols and flavonoid content in marigolds were 74.8 mg TAE/g and 85.6 mg RE/g.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these advantages of IoT application and studies for marigold growth, the research finding is only partially successful, which entails a challenge in improving the air-conditioning system in a special plant [15], such as a closed greenhouse [16], [17]. Currently, marigold flowers are the most important flowers in many economic and social sectors in Asia [18], such as Thailand, India, and Indonesia. Gardeners encounter problems with leaf diseases that affect causing the trees to deteriorate and die negatively in open areas affecting the agricultural sector [14].…”
Section: Introductionmentioning
confidence: 99%